Characteristics of AC-Base Mixture Using River Stone When Pitu Riase District, Sidrap Regency - Johannes S. Tondok; Alpius; Ika Apriyani (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
Aggregate is one of the key components that determine abilities dry carry a load of traffic if it is a river in Sidrap County with aggregates of rock and sand, potentially used as paving materials. The point of this study is to know the characteristics of river aggregate Bila, the characteristics of asphalt, the characteristics of filler, and the composition of the mixture and the AC-Base mixed characteristics. To find out the purpose of this study, conducted examinations and testing in the laboratory according to the general specifications of the 2018 Highways construction maintenance, using conventional marshall and Marshall Immersion methods. As for inspection and testing of aggregate characteristics, asphalt and fillers meet the specifications as paving materials for the road. Throughout AC-Base compound design acquired crude aggregate 53,42%, soft aggregate 37,00%, filler 4,58% with optimum asphalt 5,00%. The mixture characteristics of stability, flow, VIM, VMA, and VFB that use conventional marshall methods, and the marshall stability value are leftover from the test marshall immersion meet general specifications of the 2018 Highways construction maintenance that is 96,52% ≥ 90,00%.